Cement paste composition and use thereof

CN122977759APending Publication Date: 2026-10-27CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510524499.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

CN102124075B公开了一种在井中使用的导电水泥配方,通过水泥、水、碳纤维和石墨进行配浆,具有较好的导电率和抗剪强度,但无法满足井下作业对水泥浆弹韧性和流动性的需求

Benefits of technology

[0010](1)本发明所述的水泥浆组合物,相对传统固井水泥浆,具有稳定的导电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005374886160000111
    Figure BDA0005374886160000111
  • Figure BDA0005374886160000112
    Figure BDA0005374886160000112
  • Figure BDA0005374886160000113
    Figure BDA0005374886160000113
Patent Text Reader

Abstract

The application relates to the field of oil and gas field cementing cement slurry, and discloses a cement slurry composition and application thereof, the cement slurry composition comprising: oil well cement, a toughening agent, a carbon-based toughening resistance-reducing material, a conductive material and a fluid loss control retarder; wherein the weight ratio of the carbon-based toughening resistance-reducing material to the conductive material is 1:3-180; the resistivity of the conductive material is 2-25 mu omega*cm; the resistivity of the carbon-based toughening resistance-reducing material is 20*10 ‑3 -100*10 ‑3 mu omega*cm; and the ratio of the resistivity of the conductive material to the resistivity of the carbon-based toughening resistance-reducing material at 20 DEG C is 100-200:1.The cement slurry composition has stable conductive performance, good toughness, high early strength and good fluidity compared with traditional cementing cement slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement slurry for cementing wells in oil and gas fields, and more specifically, to a cement slurry composition and its application. Background Technology

[0002] During oil and gas well construction and production, the sealing integrity of the cement sheath is easily affected by fluctuations in downhole pressure, temperature, and other factors. This is especially true for unconventional oil and gas wells such as shale and tight sandstone wells, which require multiple large-scale hydraulic fracturing operations, subjecting the cement sheath to repeated high alternating stresses. Furthermore, gas storage wells undergo multiple cycles of intensive injection and production, subjecting the cement sheath to numerous cyclic alternating stresses and temperature changes. These downhole pressure and temperature variations can easily damage the cement sheath's sealing integrity, leading to annular pressure buildup and interlayer flow, threatening the safety and efficient development of oil and gas wells and storage facilities. Currently, it is difficult to obtain data on the integrity and flow status of the downhole cement sheath. Research has shown that converting stress, temperature, and damage signals of the cement sheath into electrical signals such as resistance can help determine the structural damage. However, traditional cement slurry systems have high resistivity, making it difficult to obtain data on gas flow and cement sheath damage through electrical signals, and they lack elasticity and toughness. Therefore, in order to ensure the integrity of the cement sheath seal and to better obtain information on the stress and damage changes of the downhole cement sheath, it is necessary to develop an intelligent conductive elastic tough cement slurry system.

[0003] In the prior art, CN114144571A discloses a method for determining well integrity, including mixing a conductive material into a fluid, introducing the fluid into the well, and allowing the conductive material to coat the surface of the underground formation to form a conductive data conduit coating. CN102124075B discloses a conductive cement formulation for use in wells, which is prepared by mixing cement, water, carbon fiber, and graphite, and has good conductivity and shear strength, but cannot meet the requirements of downhole operations for the toughness and flowability of cement slurry. CN115385621A discloses a self-inductive conductive cement composite material, which is prepared by mixing silicate cement, fly ash, defoamer, dispersant, water-reducing agent, water, sand, coarse aggregate, and conductive materials such as carbon nanotubes, carbon fibers, carbon black, or steel fibers, which reduces resistivity and improves compressive strength and flexural strength, and has good conductivity, but cannot meet the requirements of downhole operations for the toughness of cement slurry.

[0004] Currently, cement slurry can be made conductive by adding a certain concentration of conductive material. However, this cannot simultaneously meet the requirements for conductivity, elasticity, toughness, and fluidity of cement slurry, making it difficult to guarantee the integrity of the cement sheath under conditions such as large-scale hydraulic fracturing in unconventional oil and gas wells and multiple cycles of intense injection and production during gas storage operation. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems existing in the prior art and provide a cement slurry composition with strong conductivity, good elasticity and toughness, and suitable fluidity. This composition can meet the sealing integrity requirements of cement sheaths under multi-cycle alternating stress and can obtain the cement sheath sealing crossflow situation by detecting the electrical signal of the downhole cement sheath, thus ensuring the safe and efficient operation of unconventional oil and gas wells and gas storage wells.

[0006] To achieve the above objectives, the first aspect of the present invention provides a cement slurry composition comprising: oil well cement, a toughening agent, a carbon-based toughening and drag-reducing material, a conductive material, and a water loss-reducing retarder.

[0007] The weight ratio of the carbon-based toughening and drag-reducing material to the conductive material is 1:3-180; the resistivity of the conductive material is 2-25 μΩ·cm; and the resistivity of the carbon-based toughening and drag-reducing material is 20 × 10⁻⁶. -3 -100×10 -3 μΩ·cm; the resistivity ratio of the conductive material to the carbon-based toughened and drag-reducing material at 20℃ is 100-200:1.

[0008] A second aspect of the present invention provides the application of the above-described cement slurry composition in oil and gas field wells.

[0009] Through the above technical solution, the present invention can achieve at least the following beneficial effects:

[0010] (1) The cement slurry composition of the present invention has stable electrical conductivity compared with traditional cement slurry.

[0011] (2) In a preferred embodiment of the present invention, the cement slurry composition can also meet the elasticity, toughness and fluidity of cement slurry, and promote the early hydration rate of cement and the early strength. Detailed Implementation

[0012] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0013] The first aspect of the present invention provides a cement slurry composition comprising: oil well cement, toughening agent, carbon-based toughening and drag-reducing material, conductive material, and water loss-reducing retarder;

[0014] The weight ratio of the carbon-based toughening and drag-reducing material to the conductive material is 1:3-180; the resistivity of the conductive material is 2-25 μΩ·cm; and the resistivity of the carbon-based toughening and drag-reducing material is 20 × 10⁻⁶. -3 -100×10 -3 μΩ·cm; the resistivity ratio of the conductive material to the carbon-based toughened and drag-reducing material at 20℃ is 100-200:1.

[0015] In this invention, preferably, the weight ratio of the carbon-based toughening and drag-reducing material to the conductive material is 1:6-60; the resistivity of the conductive material is 5-12 μΩ·cm (for example, it can be any two values ​​formed by 5 μΩ·cm, 6 μΩ·cm, 7 μΩ·cm, 8 μΩ·cm, 9 μΩ·cm, 10 μΩ·cm, 11 μΩ·cm, and 12 μΩ·cm, or values ​​within that range); the resistivity of the carbon-based toughening and drag-reducing material is 50 × 10⁻⁶. -3 -80×10 -3 μΩ·cm (for example, 50 × 10) -3 μΩ·cm, 55×10 -3 μΩ·cm, 60×10 -3 μΩ·cm, 65×10 -3 μΩ·cm, 70×10 -3 μΩ·cm, 75×10 -3 μΩ·cm, 80×10 -3 The range formed by any two values ​​in μΩ·cm and the values ​​within the range); the resistivity ratio of the conductive material to the carbon-based toughened and drag-reducing material at 20℃ is 105-170:1.

[0016] During their research, the inventors of this invention discovered that by adding carbon-based toughening and drag-reducing materials and conductive materials in the above proportions and controlling the conductivity ratio of the two, a conductive cement slurry with stable conductivity can be obtained.

[0017] It is understood that the resistivity of the conductive material and the carbon-based toughened and drag-reducing material in this invention is measured at 20°C using the commonly used contact four-electrode method (the four electrodes are usually divided into two pairs, one pair being current electrodes for passing current and the other pair being voltage electrodes for measuring voltage).

[0018] In this invention, preferably, based on 100 parts by weight of oil well cement, the amount of toughening agent is 1-15 parts by weight (for example, it can be any two values ​​formed by 1 part by weight, 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, and 15 parts by weight, or values ​​within that range), and the amount of carbon-based toughening and drag-reducing material is 0.2-5 parts by weight (for example, it can be any two values ​​formed by 0.2 parts by weight, 0.5 parts by weight, 0.8 parts by weight, 1 part by weight, 1.2 parts by weight, 1.5 parts by weight, 1.7 parts by weight, 2 parts by weight, 2.3 parts by weight, 2.5 parts by weight, 2.8 parts by weight, 3 parts by weight, and 5 parts by weight). The amount of conductive material is 15-35 parts by weight (e.g., any two values ​​from 15, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 35 parts by weight). The amount of water loss retarder is 0.5-9 parts by weight (e.g., any two values ​​from 0.5, 2, 5, 5.5, 6, 6.5, 7, 7.5, 8, 9 parts by weight).

[0019] In a preferred embodiment of the present invention, based on 100 parts by weight of oil well cement, the amount of toughening agent is 5-10 parts by weight, the amount of carbon-based toughening and drag-reducing material is 0.5-3 parts by weight, the amount of conductive material is 18-30 parts by weight, and the amount of water loss-reducing retarder is 5-8 parts by weight.

[0020] During their research, the inventors of this invention discovered that, compared to traditional cementing slurry, the conductive cement slurry composition with the above-mentioned dosage not only has stable conductivity but also meets the requirements for elasticity, toughness, and fluidity of cementing slurry, and promotes the early hydration rate of cement, resulting in high early strength.

[0021] In this invention, based on 100 parts by weight of oil well cement, the cement slurry composition further includes: 0.2-3 parts by weight of dispersant (e.g., any two values ​​within the range of 0.2, 0.3, 0.4, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, 2.3, 2.5, 2.7, and 3 parts by weight, and values ​​within that range), and 0.1-1 parts by weight of defoamer (e.g., 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, and 0.7 parts by weight). The cement slurry composition comprises: 0.3-2.5 parts by weight of dispersant, 0.2-0.5 parts by weight of defoamer, and 50-70 parts by weight of water (e.g., any two values ​​from 0.8 parts by weight, 0.9 parts by weight, and 1 part by weight, and values ​​within that range) and 47-80 parts by weight of water (e.g., any two values ​​from 47 parts by weight, 45 parts by weight, 48 parts by weight, 50 parts by weight, 52 parts by weight, 55 parts by weight, 57 parts by weight, 60 parts by weight, 63 parts by weight, 65 parts by weight, 68 parts by weight, 70 parts by weight, 73 parts by weight, 75 parts by weight, 77 parts by weight, and 80 parts by weight, and values ​​within that range); preferably, the cement slurry composition further comprises: 0.3-2.5 parts by weight of dispersant, 0.2-0.5 parts by weight of defoamer, and 50-70 parts by weight of water.

[0022] In this invention, preferably, the toughening agent is latex and / or sulfur-cured rubber, more preferably sulfur-cured rubber; wherein, the sulfur-cured rubber can be a commonly used sulfur-cured rubber in the art, such as sulfur-cured styrene-butadiene rubber, etc.

[0023] In this invention, preferably, the carbon-based toughening and drag-reducing material is selected from at least one of graphene oxide, graphene, carbon nanotubes and carbon fibers, and more preferably graphene oxide and / or graphene.

[0024] In a preferred embodiment of the present invention, the method for preparing the graphene includes: using inexpensive graphite powder, and through ball milling, effectively opening its edges in a graphite powder system with a grinding aid attached by means of mutual repulsion, overcoming the van der Waals forces between layers to orderly exfoliate, thereby obtaining graphene.

[0025] In a preferred embodiment of the present invention, the method for preparing the graphene oxide may be: to activate and oxidize the graphene obtained above to obtain graphene oxide.

[0026] In a preferred embodiment of the present invention, the ball milling method is a ball milling method known in the art, and the grinding aid is a commonly used grinding aid in the art. For example, the grinding aid may be magnesium oxide and / or zirconium oxide.

[0027] In a preferred embodiment of the present invention, the conditions for preparing modified graphene include: a ball milling time of 4-6 h (for example, it can be any two values ​​from 4 h, 4.5 h, 5 h, 5.5 h, 6 h, or any value within that range), and a rotation speed of 600-800 r / min (for example, it can be any two values ​​from 600 r / min, 620 r / min, 640 r / min, 680 r / min, 700 r / min, 720 r / min, 740 r / min, 760 r / min, 780 r / min, 800 r / min, or any value within that range).

[0028] In a preferred embodiment of the present invention, the carbon-based toughening and drag-reducing material acts as an attachment for the precipitation and crystallization of cement particle hydration products in the solution, and plays a nucleation role in the cement hydration process, which can accelerate the hydration rate of tricalcium silicate, thereby improving the early strength of cement.

[0029] In this invention, preferably, the conductive material is selected from iron powder and / or steel fiber, and more preferably reduced iron powder.

[0030] In this invention, preferably, the average particle size of the conductive material is 22-90 μm (for example, it can be any two values ​​formed by 22 μm, 23 μm, 25 μm, 28 μm, 30 μm, 33 μm, 35 μm, 37 μm, 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, or values ​​within that range), and more preferably 25-50 μm.

[0031] In this invention, preferably, the carbon content of the conductive material is ≤0.01wt% (for example, it can be any two values ​​from 0.001wt%, 0.002wt%, 0.003wt%, 0.004wt%, 0.005wt%, 0.006wt%, 0.007wt%, 0.008wt%, 0.009wt%, 0.01wt%, or any value within that range), and the water content is ≤0.01wt% (for example, it can be any two values ​​from 0.001wt%, 0.002wt%, 0.003wt%, 0.004wt%, 0.005wt%, 0.006wt%, 0.007wt%, 0.008wt%, 0.009wt%, 0.01wt%, or any value within that range).

[0032] In a preferred embodiment of the present invention, the carbon-based toughening and drag-reducing material and the conductive material overlap each other, which improves the conductivity of the cement stone. If only one of them is used, they cannot be connected after dispersion, and the effect of improving conductivity is limited. The toughening agent and the carbon-based toughening and drag-reducing agent are used in combination, which further reduces the elastic modulus of the cement stone and improves its elasticity and toughness.

[0033] In this invention, preferably, the water loss retarder can be selected from at least one of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) polymer, ketone-aldehyde condensation polymer, and polyvinyl alcohol (PVA) compounds, more preferably 2-acrylamide-2-methylpropanesulfonic acid polymer; wherein, the 2-acrylamide-2-methylpropanesulfonic acid polymer, aldehyde-ketone condensation polymer, and polyvinyl alcohol can be commonly used agents in the art.

[0034] The inventors of this invention have discovered that when the mass ratio of graphene, sulfur-cured rubber, and reduced iron powder is 1:8-20:35-50, the electrical conductivity is more stable, the elasticity and toughness are better, and the early strength is higher.

[0035] In a preferred embodiment of the present invention, the preparation method of the 2-acrylamide-2-methylpropanesulfonic acid polymer includes: initiating a reaction by adding 0.4% (mass fraction) of a water-soluble azo initiator (azobisisobutyramidine hydrochloride) to 2-acrylamide-2-methylpropanesulfonic acid and itaconic acid in a monomer mass ratio of 73:27 at a pH of 10 and a temperature of 60°C; the reaction conditions are not particularly limited, as long as they can meet the reaction requirements, for example, the reaction time can be 0.5-1h.

[0036] In this invention, the dispersant can be a commonly used dispersant in cement slurry, for example, a polycarboxylic acid dispersant and / or a sulfur sulfide aldehyde ketone condensate, preferably a polycarboxylic acid dispersant (e.g., at least one of polyacrylic acid, polymethacrylic acid and hydrolyzed maleic anhydride HPMA).

[0037] In this invention, the defoamer can be a defoamer commonly used in cement slurry in the art, for example, it can be at least one of polyether defoamer, polysiloxane defoamer and polyether modified silicone oil defoamer, preferably a polyether defoamer (for example, at least one of GP type polyether defoamer, GPE type polyether defoamer and GPES type polyether defoamer).

[0038] According to some preferred embodiments of the present invention, the density of the cement slurry composition is 1.80-1.95 g / cm³ under conditions of 20-110°C and 10-60 MPa. 3 The cement slurry has a fluidity ≥18cm, a water separation rate ≤2mL, and a density difference ≤0.01g / cm³. 3 .

[0039] A second aspect of the present invention provides the application of the above-described cement slurry composition in oil and gas field wells.

[0040] In a preferred embodiment of the present invention, the cement slurry composition is mainly used in oil and gas wells during the cementing process.

[0041] In this invention, the cement slurry composition is applied at a temperature of 25-110°C (for example, it can be any two values ​​formed by 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, and values ​​within that range).

[0042] In this invention, the pressure of the cement slurry composition during application is 0-100 MPa (for example, it can be any two values ​​formed by 1 MPa, 5 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 52 MPa, 55 MPa, 60 MPa, 65 MPa, 70 MPa, 75 MPa, 80 MPa, 85 MPa, 90 MPa, 95 MPa, 100 MPa, and the values ​​within that range).

[0043] The present invention will be described in detail below through examples. In the following examples, the cement is Jiahua G-grade oil well cement, purchased from Sichuan Jiahua Cement Plant. The sulfur-cured rubber is a commercially available product of brand name SCE, purchased from Dezhou Continental Shelf Company; the graphene is a commercially available product of brand name SCG, purchased from Dezhou Continental Shelf Company; the graphene oxide is a commercially available product of brand name SCGO, purchased from Dezhou Continental Shelf Company; the GP-type glycerol polyether defoamer is from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.; the 2-acrylamide-2-methylpropanesulfonic acid polymer water loss retarder is brand name DZH-2, purchased from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.; and the polycarboxylic acid dispersant is brand name JSS, purchased from Dezhou Continental Shelf Petroleum Engineering Technology Co., Ltd.

[0044] The fluidity was measured according to GB / T19139—2012 Oil Well Cement Test Method.

[0045] The compressive strength was measured according to GB / T 19139—2012 Oil Well Cement Test Method.

[0046] The resistivity of the conductive material and the carbon-based toughened and drag-reducing material was measured at 20°C using a contact four-electrode method.

[0047] The elastic modulus was measured according to GB / T 19139—2012 Oil Well Cement Test Method.

[0048] Example 1

[0049] 100 parts by weight of Grade G oil well cement, 8 parts by weight of sulfur-cured rubber, 0.5 parts by weight of graphene, and 23 parts by weight of reduced iron powder with an average particle size of 30 μm (resistivity of 6 μΩ·cm) were mixed evenly to obtain a mixture. 0.4 parts by weight of polycarboxylate dispersant, 8 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid polymer water loss retarder, 0.2 parts by weight of GP type glycerol polyether defoamer, and 52.7 parts by weight of water were mixed to obtain slurry water, wherein the resistivity ratio of graphene to reduced iron powder was 1:105. The slurry water and the above mixture were then stirred and mixed in a high-speed mixer to obtain cement slurry system J-1. Cement slurry system J-1 was cured at 90℃ for 24 hours and 7 days to obtain cement stone S-1.

[0050] Example 2

[0051] This embodiment operates on the same procedure as Embodiment 1, except that: 10 parts by weight of sulfur-cured rubber, 3 parts by weight of graphene, and 30 parts by weight of reduced iron powder (with an average particle size of 30 μm and a resistivity of 6 μΩ·cm) are added to obtain cementing slurry system J-2. Cementing slurry system J-2 is cured at 90℃ for 24 hours and 7 days to obtain cement stone S-2.

[0052] Example 3

[0053] The operation process of this embodiment is the same as that of Embodiment 1, except that: the amount of sulfur-cured rubber added is 5 parts by weight, the amount of graphene added is 0.2 parts by weight, and the amount of reduced iron powder with an average particle size of 30 μm is 15 parts by weight, resulting in cementing slurry system J-3. Cementing slurry system J-3 is cured at 90℃ for 24 hours and 7 days to obtain cement stone S-3.

[0054] Example 4

[0055] The operation process of this embodiment is the same as that of Embodiment 1, except that graphene is replaced with graphene oxide to obtain cementing slurry system J-4. Cementing slurry system J-4 is cured at 90℃ for 24 hours and 7 days to obtain cement stone S-4.

[0056] Comparative Example 1

[0057] The operation process of this comparative example is the same as that of Example 1, except that sulfur-cured rubber, graphene, and reduced iron powder were not added, resulting in cementing slurry system J-5. Cementing slurry system J-5 was cured at 90°C for 24 hours and 7 days to obtain cement stone S-5.

[0058] Comparative Example 2

[0059] The operation process of this comparative example is the same as that of Example 1, except that no graphene was added, resulting in cementing slurry system J-6. Cementing slurry system J-6 was cured at 90°C for 24 hours and 7 days to obtain cement stone S-6.

[0060] Comparative Example 3

[0061] The operation process of this comparative example is the same as that of Example 1, except that reduced iron powder with an average particle size of 30 μm was not added, resulting in cementing slurry system J-7. Cementing slurry system J-7 was cured at 90°C for 24 hours and 7 days to obtain cement stone S-7.

[0062] Comparative Example 4

[0063] The operation process of this comparative example is the same as that of Example 1, except that sulfur-cured rubber was not added, resulting in cementing slurry system J-8. Cementing slurry system J-8 was cured at 90°C for 24 hours and 7 days to obtain cement stone S-8.

[0064] Comparative Example 5

[0065] The operation process of this comparative example is the same as that of Example 1, except that the amount of materials added to the cementing slurry system is changed to: 20 parts by weight of sulfur-cured rubber, 10 parts by weight of graphene, 20 parts by weight of reduced iron powder with an average particle size of 30 μm (resistivity of 6 μΩ·cm), and 15 parts by weight of 2-acrylamide-2-methylpropanesulfonic acid polymer water loss retarder, resulting in cementing slurry system J-9. Cementing slurry system J-9 is cured at 90℃ for 24 hours and 7 days to obtain cement stone S-9.

[0066] Comparative Example 6

[0067] The operation process of this comparative example is the same as that of Example 1, except that the amount of graphene added is 10 parts by weight.

[0068] Test case

[0069] The cement slurry and cement stone prepared above were tested according to GB / T 19139—2012 Oil Well Cement Test Method for fluidity, compressive strength, water separation, and elastic modulus of the cement slurry. The resistivity (ρ1) of the cement slurry was tested using a contact four-electrode method at 60℃. After the cement slurry was cured at 60℃ until it lost weight, water was introduced at a rate of 5 mL / min, and the resistivity (ρ2) of the cement slurry after crossflow was tested using a contact four-electrode method.

[0070] The stability of cement slurry can be characterized by the amount of water separation and the density difference between the upper and lower parts. The density difference is determined as follows: the well-stirred cement slurry is poured into a 250ml graduated cylinder and left to stand for 2 hours. The cement slurry in the graduated cylinder is then poured out in three parts: upper, middle, and lower. The density of each part is measured. The difference between the density of the lower part and the upper part is called the density difference. The test results are shown in Table 1.

[0071] Table 1

[0072]

[0073] By comparing the performance test results of the above embodiments and comparative examples, it can be concluded that: in the embodiments, adding carbon-based toughening and resistance-reducing materials and conductive materials with specific electrical conductivity ratios in a certain proportion can reduce the elastic modulus of cement stone on the one hand, accelerate the early cement hydration rate and improve the early compressive strength on the other hand, and at the same time, reduce resistivity and increase conductivity.

[0074] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A cement slurry composition, characterized in that, The cement slurry composition includes: oil well cement, toughening agent, carbon-based toughening and drag-reducing material, conductive material, and water loss-reducing retarder; The weight ratio of the carbon-based toughening and drag-reducing material to the conductive material is 1:3-180; the resistivity of the conductive material is 2-25 μΩ·cm; and the resistivity of the carbon-based toughening and drag-reducing material is 20 × 10⁻⁶. -3 -100×10 -3 μΩ·cm; the resistivity ratio of the conductive material to the carbon-based toughened and drag-reducing material at 20℃ is 100-200:

1.

2. The composition according to claim 1, wherein, The weight ratio of the carbon-based toughening and drag-reducing material to the conductive material is 1:6-60; the resistivity of the conductive material is 5-12 μΩ·cm; and the resistivity of the carbon-based toughening and drag-reducing material is 50 × 10⁻⁶. -3 -80×10 -3 μΩ·cm; The resistivity ratio of the conductive material to the carbon-based toughened and drag-reducing material at 20°C is 105-170:1; And / or, based on 100 parts by weight of oil well cement, the amount of toughening agent is 1-15 parts by weight, the amount of carbon-based toughening and drag-reducing material is 0.2-5 parts by weight, the amount of conductive material is 15-35 parts by weight, and the amount of water loss-reducing retarder is 0.5-9 parts by weight. Preferably, based on 100 parts by weight of oil well cement, the amount of toughening agent is 5-10 parts by weight, the amount of carbon-based toughening and drag-reducing material is 0.5-3 parts by weight, the amount of conductive material is 18-30 parts by weight, and the amount of water loss-reducing retarder is 5-8 parts by weight.

3. The composition according to claim 1 or 2, wherein, The toughening agent is latex and / or sulfur-cured rubber, preferably sulfur-cured rubber; And / or, the carbon-based toughening and drag-reducing material is selected from at least one of graphene oxide, graphene, carbon nanotubes and carbon fibers, preferably graphene oxide and / or graphene.

4. The composition according to claim 1 or 2, wherein, The conductive material is selected from iron powder and / or steel fiber, preferably reduced iron powder.

5. The composition according to claim 1 or 2, wherein, The water loss retarder is at least one of 2-acrylamide-2-methylpropanesulfonic acid polymer, ketone-aldehyde condensation polymer and polyvinyl alcohol compound, preferably 2-acrylamide-2-methylpropanesulfonic acid polymer.

6. The composition according to claim 1 or 2, wherein, Based on 100 parts by weight of oil well cement, the cement slurry composition further includes: 0.2-3 parts by weight of dispersant, 0.1-1 parts by weight of defoamer and 47-80 parts by weight of water, preferably 0.3-2.5 parts by weight of dispersant, 0.2-0.5 parts by weight of defoamer and 50-70 parts by weight of water.

7. The composition according to claim 1 or 2, wherein, The conductive material has an average particle size of 22-90 μm, preferably 25-50 μm; And / or, the carbon content of the conductive material is ≤0.01wt%, and the water content is ≤0.01wt%.

8. The application of the cement slurry composition according to any one of claims 1-7 in oil and gas field wells.

9. The application according to claim 8, wherein, The cement slurry composition is applied at a temperature of 25-110°C.

10. The application according to claim 8 or 9, wherein, The pressure of the cement slurry composition during application is 0-100 MPa.

Citation Information

Patent Citations

  • Conductive cement formulation and application for use in well

    CN102124075B

  • Self-induction conductive cement composite material and preparation method thereof

    CN115385621A